2004
DOI: 10.1159/000077741
|View full text |Cite
|
Sign up to set email alerts
|

The Sesto Fiorentino Study: Point and One-Year Prevalences of Psychiatric Disorders in an Italian Community Sample Using Clinical Interviewers

Abstract: Background: It has been argued that lay interviewers’ use of fully-structured interviews could lead to a diagnostic pattern different to that by treating physicians. Clinical interviewers in community samples should probably identify cases that are closer to those seen in clinical settings. The greatest advantage of using clinical interviewers consists of the immediate assessment of a possible psychopathology, i.e. the evaluation of current disorders. Methods: Two thousand three hundred and sixty-three citizen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
65
6
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(101 citation statements)
references
References 21 publications
27
65
6
3
Order By: Relevance
“…However, in contrast with findings from other studies [3,12,14,19,21,44,46] that reported prevalence estimates of externalizing disorders of 4-7%, the percentage of Italian adolescents with these disorders was only 1.2%. These data are consistent with findings on Italian adults [15,18,28]. In particular, the recent ESEMeD-WMH study [15] indicates that compared to other European countries and Figures in boldface reflect statistically significant differences the US, in Italy the prevalence rates of anxiety (5.8% CI 4.5-7.1%) and mood disorders (3.8% CI 3.1-4.5%) are lower and those of impulse control (0.3% 95% CI 0.1-0.5) and substance use (0.1% 95% CI 0-0.2) disorders are the lowest.…”
Section: J Prevalence Of Mental Disorders In Adolescentssupporting
confidence: 94%
“…However, in contrast with findings from other studies [3,12,14,19,21,44,46] that reported prevalence estimates of externalizing disorders of 4-7%, the percentage of Italian adolescents with these disorders was only 1.2%. These data are consistent with findings on Italian adults [15,18,28]. In particular, the recent ESEMeD-WMH study [15] indicates that compared to other European countries and Figures in boldface reflect statistically significant differences the US, in Italy the prevalence rates of anxiety (5.8% CI 4.5-7.1%) and mood disorders (3.8% CI 3.1-4.5%) are lower and those of impulse control (0.3% 95% CI 0.1-0.5) and substance use (0.1% 95% CI 0-0.2) disorders are the lowest.…”
Section: J Prevalence Of Mental Disorders In Adolescentssupporting
confidence: 94%
“…Three populationbased studies conducted in Italy and USA, reported lifetime prevalence rates of comorbid OCD in BD patients ranging between 11.1% and 21% (3,23,24). In hospital-based studies, the lifetime prevalence of comorbid OCD in BD patients ranged between 1.8% and 35.1% (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) depending on the features of the BD study population included (schizoaffective disorder, bipolar type).…”
Section: Included Studiesmentioning
confidence: 99%
“…Population-based studies reported lifetime prevalence rates of comorbid BD-OCD ranging between 11.1 and 21%. [1][2][3] The prevalence of OCD may be masked by presence of manic or depressive symptoms in BD, which is evident from data in remitted patients where the reported prevalence of comorbid OCD is quite high (35 to 38.6%). [4][5][6] In children with BD, the prevalence of OCD ranges between 20.7 and 46.9%.…”
Section: Introductionmentioning
confidence: 99%